Position and Jurisdiction of Military Courts in Indonesia - Tiarsen Buaton; Agustinus Purnomo Hadi; Prastopo Prastopo; M. Ali Ridho; Ateng Karsoma (Penerbit Goodwood, 2024)
Purpose: Analyze the scope of jurisdiction and authority of military courts over cases involving military personnel and other related issues adan Assess how military courts interact with civilian courts and the implications for justice and military discipline. Method: Conduct interviews with legal experts, military personnel, and practitioners in the field of military justice to gather insights on the functioning and challenges of military courts. Result: A detailed explanation of how military courts are situated within Indonesia's judicial hierarchy, including their relationship with civilian courts and the constitutional basis for their existence. An outline of the specific types of cases military courts are authorized to handle, including criminal offenses committed by military personnel, disciplinary matters, and other related issues. Insights into how military courts operate in practice, including procedural aspects, the role of military judges, and the enforcement of military justice.